FACTORS AFFECTING VILLAGE OWNED ENTERPRISE INCOME IN HULAWA VILLAGE, PAGUYAMAN DISTRICT, BOALEMO DISTRICT: FAKTOR-FAKT0R YANG MEMPENGARUHl PENDAPATAN BADAN USAHA MlLIK DESA Di DESA HULAWA KECAMATAN PAGUYAMAN KABUPATEN BOALEMO - Ningsi ningsi dakio; Ikram Muhammad; Karlina Napu (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine 1) internal factors such as business management, business location, business capital, length of business and working hours that affect the income of Village-Owned Enterprises in Hulawa Village 2) To determine external factors that affect the income of Village-owned Enterprises in Hulawa Village such as natural resources, economic conditions, culture, security which affect the increase in Hulawa BUMDes income. This research is a type of descriptive research with a qualitative approach. The data analysis technique used is data analysis technique by processing data using the Miles and Huberman Models. The research informants were the Head of BUMDes, Secretary of BUMDes, Treasurer of BUMDes, Head of Hulawa Village and the Community (3 people). Data collection methods used in this study were observation, in-depth interviews and documentation. The data analysis technique used is data analysis technique by processing data using the Miles and Huberman Models. The results of the study are 1) Internal factors that have been optimal and have an effect on BUMDes income in Hulawa Village, Paguyaman District, Boalemo Regency are business location, business capital, length of business and working hours. But the business management factor is not yet optimal, because business management still needs to be improved, especially in BUMDes business management. 2) External factors that have been optimal and have influenced BUMDes revenue in Hulawa Village, Boalemo District, are local culture and the security of BUMDes management that has been supported. But the internal factors of natural resources and economic conditions are not optimal. Because the available natural resources have not been utilized properly while the economic conditions of the Hulawa Village community are the lower middle class such as farmers, traders and miner.